Code of ethics
The coach`s primary role is to facilitate the process of individual development through achievement of Athletic potential. This role accepts the athletes` long term interests as of greater importance than short term athletic considerations. To fulfil this role the coach must behave in an ethical manner. By becoming a member of the ATFCA, a coach agrees to be held accountable for any breach of the 14 points mentioned in this article.